Social Contract-2030 – a Modern Institution in Implementing the Interaction Between the State, Society and Business - Ponedelkov Aleksandr V.; Kuzina Svetlana I.; Cherkasova Tatyana P. (Вестник Волгоградского государственного университета. Серия 4. История, регионоведение, международные отношения, 2016)
The article is devoted to analysis of formation processes of interaction between the state, civil society and business in Russia. As an empirical basis the authors use the results of sociological research conducted by Public Opinion Fund in 2015, scientists of the South-Russian Institute of Management – Branch of Russian Presidential Academy of National Economy and Public Administration in 2012 and 2016. 44 % of respondents in the regions expressed a preference for the social partnership of government, business and civil society. The authors believe that the implementation of the mission of the Social Contract-2030 is possible through the mechanism of public-private partnership (PPP), which is the most promising and effective institution in modern economicpolitical condition of Russia. The strategic goals of the state consist in providing transfer of the country to the path of innovative development, aimed at reducing the export-resource dependence of the country in the context of the mission of Social Contract-2030 and the national security strategy of the country is impossible without formation of a partnership between the state, companies and commercial structures. Each of the members of the partnership provides a contribution to the implementation of the project. The business structure for its part contributes investment funds, human resources, effective business technologies, flexibility and responsiveness in decision-making, innovation and other private initiatives and available resources. The state in turn provides a partnership through their powers with necessary legal and institutional resources that ensure protective measures for the formation of a competitive and low-risk business. The main task of civil society is to help citizens in solving social problems and the implementation of control over the power structures in the fulfillment of social obligations of the state. The question of increasing the efficiency of mechanisms of Social contract-2030 implementation between the state, society, and business implies transparency of activities of public authorities and effective management of results.